Rosai-Dorfman disease as a rare cause of cervical lymphadenopathy – case report and literature review - Aleksandra Miękus; Joanna Stefanowicz; Grażyna Kobierska-Gulida; Elżbieta Adamkiewicz-Drożyńska (Central European Journal of Immunology, 2018)
Rosai-Dorfman disease (RDD), also known as sinus histiocytosis with massive lymphadenopathy, is a rare, benign clinical entity of unknown cause. RDD is characterised by the overproduction and accumulation of histiocytes, primarily in the lymph nodes, although it may affect every organ and system. It predominantly affects children and young adults. Typically, patients are in good general condition, with massive cervical lymphadenopathy and fever. In about 40% of cases extranodal localisation of RDD is diagnosed. In laboratory tests the most common abnormalities are increased erythrocyte sedimentation rate (ESR), leukocytosis with neutrophilia, normocytic anaemia, and hypergammaglobulinaemia. Histopathological examination remains the mainstay of diagnosis – lymph nodes have massive sinusoidal dilation, containing histiocytes positive for S-100 and CD68, and negative for CD1a. Most patients do not require treatment as spontaneous remissions are observed. We present a brief review of the literature and the case of a six-year-old boy with cervical lymphadenopathy diagnosed with RDD. So far, the patient has not required systemic treatment and has been kept under observation.